Harm, Liberty, and Disability - Melinda Rosenberg (Disability Studies Quarterly, 2009)
Among the works of man which human life is rightly employed in perfecting and beautifying, the first in importance surely is man himself...Human nature is not a machine to be built after a model, and set to do exactly the work prescribed for it, but a tree, which requires to grow and develop itself on all sides, according to the tendency of the inward forces which make it a living thing (Mill 1978, pp. 56-7).